The adequacy of Malaysian law on doctor's duty to disclose risk of treatment to patients / Nurul Najwa Abdul Hamid, Norsyahida Mohd Nor Suhaimi and Nur Zhafarina Mohd Zaid - Abdul Hamid, Nurul Najwa; Mohd Nor Suhaimi, Norsyahida; Mohd Zaid, Nur Zhafarina (2009)
This legal research is conducted with an aim to study and analyze the adequacy of Malaysian law on doctor's duty to disclose risk of treatment to patients. Basically, there is no relevant section in this statute explains about doctor's duty to disclose risks of treatment to the patient and its punishment. Since then, there is no specific standard of care relating to this duty to be applied in Malaysia. Thus, this research will focus on the adequacy of the existing laws and to make some recommendations to amend the existing law in Malaysia. The scope of this legal research is on the adequacy of law specifically on the doctor's duty to disclose risk of treatment in Malaysia. This legal research will be based on the secondary sources from the Law Library of University Teknologi MARA (UiTM). Legislation, cases articles, books and other appropriate sources that relates to the duty to disclose risk of treatment are also used. Besides, structured interviews were conducted to gather information and views from the academicians and practitioner doctor in regards of duty to disclose risk of treatment. It is hoped that this legal research will provide a comprehensive discussion on the adequacy of Malaysian law on the doctor's duty to disclose risk of treatment to the patients and proposed amendments or suggestion to the current law to standardize this duty.